2016
DOI: 10.1016/j.eurpsy.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress and Youth Violence Perpetration: a Population-Based Cross-Sectional Study

Abstract: In addition to trauma, posttraumatic stress is related to violent outcomes. However, specific symptom clusters of PTSD seem differently related to violent behaviours and they do not fully explain a trauma-violence link. Specific interventions to improve emotion regulation skills may be useful particularly in boys with elevated PTSD dysphoric arousal in order to break up the cycle of violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 48 publications
2
29
0
1
Order By: Relevance
“…The direct impact of trauma‐related distress on physical aggression found in the current study underscores the unique contribution of trauma‐related distress on later aggression, even after controlling for aggression at previous waves. The current findings are consistent with past cross‐sectional studies that have found a strong association between trauma‐related distress and aggression (Abate et al, ; Aebi et al, ; Marsee, ). Given the high prevalence rates of childhood victimization and exposure to violence, assessment of trauma‐related distress should be more widespread within violence prevention and intervention research.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The direct impact of trauma‐related distress on physical aggression found in the current study underscores the unique contribution of trauma‐related distress on later aggression, even after controlling for aggression at previous waves. The current findings are consistent with past cross‐sectional studies that have found a strong association between trauma‐related distress and aggression (Abate et al, ; Aebi et al, ; Marsee, ). Given the high prevalence rates of childhood victimization and exposure to violence, assessment of trauma‐related distress should be more widespread within violence prevention and intervention research.…”
Section: Discussionsupporting
confidence: 92%
“…The association between trauma‐related distress and various forms of aggression is supported by numerous cross‐sectional studies (e.g., Abate, Marshall, Sharp, & Venta, ; Aebi et al, ; Marsee, ). Two longitudinal studies found that trauma‐related distress mediated the relation between traumatic experiences and externalizing behaviors, including dating violence (Wolfe et al, ) and symptoms of conduct disorder, oppositional defiant disorder, and attention deficit/hyperactivity disorder (Cromer & Villodas, ).…”
Section: Introductionmentioning
confidence: 93%
“…Several international studies including one in the USA (Carlson & Schafer, 2010) and one in South Africa (Richter et al, 2018) found that across the prison population, the majority of perpetrators had been victims of childhood trauma including witness to or victim of interpersonal violence. In a nationally representative US sample, 99% of perpetrators of violence had reported being victims of violence themselves (Maschi & Bradley, 2008) and other studies have found prevalence rates of between 60% and 90% of exposure to violence amongst young offenders (Aebi et al, 2017).…”
Section: Violence: the Problemmentioning
confidence: 91%
“…In an European population-based survey of over 6,000 ninth graders in Switzerland, it was found that those who experienced trauma were significantly more likely to engage in violence and males, particularly those with high levels of dysphoric arousal and low levels of anxiety, were particularly at risk of perpetrating violence (Aebi et al, 2017). Although around 85% of the general population will recover following trauma, this is greatly reduced in the justice population with estimates as low as 20% depending on the nature of the trauma and dose-response effects (Buckingham, 2016).…”
Section: Violence: the Problemmentioning
confidence: 99%
“…Furthermore, traumatic experiences of the children and adolescents may increase the risk of escalating interactions and physical violence against youth welfare staff [34,35]. Much of the abundant literature on the association between traumatic experiences and auto-aggression has come to the conclusion that traumatic experiences in childhood are a prominent risk factor for aggressive behaviour and conduct problems throughout the course of a survivors' life [12,[36][37][38][39][40][41][42][43]. The close correlation could be explained, for example, by the misinterpretation of specific social interactions [44][45][46][47][48], model learning, deficits in implicit and explicit emotion regulation [49], especially the selfregulation of aggressive impulses, deficits in the ability to mentalise and be empathic [50] .…”
Section: Introductionmentioning
confidence: 99%